DO YOU REMEMBER THE WORDS? DUAL-CODING METHOD ON LONG-TERM MEMORY - Aryanto, Christ Billy (Faculty of Psychology, Diponegoro University, 2020)
For students, long-term memory is required for individuals to study at various levels of education. An effective method is needed to help student to remember. This study aims to determine the dual-coding method on long-term memory in two levels of education: primary school and university. The first study was conducted on 60 primary school students and the second study was conducted on 81 university students, each divided into experimental group and control group. The two groups were shown 10 concrete nouns with the experimental group displayed along with the picture and only the word for the control group. Each word was displayed for 3 seconds. The results showed that the experimental group remembered more words in the first study, t(58) = 4.386, p < .05; and the control group remembered more words in the second study, t(79) = -3.036, p < .05. Therefore, the dual-coding method affects the long-term memory of primary school students but not on university students.